KARAKTERISASITEPUNG TAPIOKA LAKTAT - Damat . (Jurnal Gamma, 2010)
Consumption of wheat flour in our country from year to year continue to increase. Ironicallyuntil now wheat flour as raw material still completely imports. In 2007 imports of wheat has reached4.4 million tons. So for those reasons, it is necessary to substitution of wheat flour with other flourof tubers are widely planted by our society. One source of potential tubers is starch that can beprocessed into starch. The major problem of tapioca flour has no gluten so is relatively difficult toexpand. For those reasons, need modification of starch.The general objective of this research is to find a method of starch synthesis of lactate byphysical and chemical characteristics of wheat flour-like characteristics. The specific objective ofthis research is to improve the physical and chemical characteristics of starch so that it hascharacteristics that resemble the characteristics of wheat flour. The results showed that thefermentation for 12 hours to 60 hours of power a real influence on the development of the flourproduced kasava. Additionally, improvement of physical and chemical properties of flour kasavaresult of natural fermentation treatment. This allows a variety of products can be made using rawmaterials from kasava flour fermentation. While the cake flour produced from the fermentationkasava not much different from the cakes made from flour or it can be said nearly matching thequality of wheat flour.